Variable Number Tandem Repeat Profiling of Mycobacterium ulcerans Reveals New Genotypes in Buruli Ulcer Endemic Communities in Ghana and Côte d’Ivoire - Gyamfi, Elizabeth; Dogbe, Magdalene Amerl; Quaye, Charles; Affouda, Abel Adjet; Kyei-Baffour, Edwin; Awuku-Asante, Daisy; Sarpong-Duah, Mabel; Mosi, Lydia (Frontiers in Microbiology, 2022)
Buruli ulcer (BU), a necrotic skin disease caused by Mycobacterium ulcerans, is mainly prevalent in West Africa, but cases have also been reported in other tropical parts of the world. It is the second most common mycobacterial disease after tuberculosis in Ghana and Côte d’Ivoire. Heterogeneity among M. ulcerans from different geographical locations has not been clearly elucidated, and some studies seem to suggest genetic differences between M. ulcerans in humans and in the environment. This study aimed at identifying genetic differences among M. ulcerans strains between two BU endemic countries: Ghana and Côte d’Ivoire. Clinical samples consisting of swabs, fine needle aspirates, and tissue biopsies of suspected BU lesions and environmental samples (e.g., water, biofilms from plants, soil, and detrital material) were analyzed. BU cases were confirmed via acid fast staining and PCR targeting the 16S rRNA, IS2404, IS2606, and ER domain genes present on M. ulcerans. Heterogeneity among M. ulcerans was determined through VNTR profiling targeting 10 loci. Eleven M. ulcerans genotypes were identified within the clinical samples in both Ghana and Côte d’Ivoire, whiles six M. ulcerans genotypes were found among the environmental samples. Clinical M. ulcerans genotypes C, D, F, and G were common in both countries. Genotype E was unique among the Ghanaian samples, whiles genotypes A, Z, J, and K were unique to the Ivorian samples. Environmental isolates were found to be more conserved compared with the clinical isolates. Genotype W was observed only among the Ghanaian environmental samples. Genotype D was found to be prominent in both clinical and environmental samples, suggesting evidence of possible transmission of M. ulcerans from the environment, particularly water bodies and biofilms from aquatic plants, to humans through open lesions on the skin.